2016
DOI: 10.1159/000446563
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Prenatal Nicotine Exposure Alters METH-Induced Hyperactivity, Conditioned Hyperactivity, and BDNF in Adult Rat Offspring

Abstract: In the USA, approximately 15% of women smoke tobacco cigarettes during pregnancy. In utero tobacco smoke exposure produces somatic growth deficits like intrauterine growth restriction and low birth weight in offspring, but it can also negatively influence neurodevelopmental outcomes in later stages of life, such as an increased incidence of obesity and drug abuse. Animal models demonstrate that prenatal nicotine (PN) alters the development of the mesocorticolimbic system, which is important for organizing goal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 71 publications
(92 reference statements)
2
8
0
1
Order By: Relevance
“…Decades of research on conventional cigarette smoke have reported the toxicological effects of smoking and nicotine on brain development. For example, studies utilizing various exposure paradigms to assess the developmental effects of prenatal and/or postnatal nicotine exposure in rodents reported increased hyperactivity (Lacy et al 2016;Newman et al 1999), impaired cognitive ability in terms of memory and attention, altered pre-pulse inhibition (Alkam et al 2013;Zhang et al 2018), and increased prevalence of anxiety-or depressive-like behaviors in adulthood (Lee et al 2016;Pinheiro et al 2015;Zhang et al 2019). Importantly, some of these behavioral alterations (e.g., increased activity) were reported in offspring of pregnant mice exposed to 2.4% nicotine through e-cigarette aerosol exposure (Smith et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Decades of research on conventional cigarette smoke have reported the toxicological effects of smoking and nicotine on brain development. For example, studies utilizing various exposure paradigms to assess the developmental effects of prenatal and/or postnatal nicotine exposure in rodents reported increased hyperactivity (Lacy et al 2016;Newman et al 1999), impaired cognitive ability in terms of memory and attention, altered pre-pulse inhibition (Alkam et al 2013;Zhang et al 2018), and increased prevalence of anxiety-or depressive-like behaviors in adulthood (Lee et al 2016;Pinheiro et al 2015;Zhang et al 2019). Importantly, some of these behavioral alterations (e.g., increased activity) were reported in offspring of pregnant mice exposed to 2.4% nicotine through e-cigarette aerosol exposure (Smith et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As an example, maternal cigarette smoking during pregnancy influences BDNF expression in the prenatally exposed offspring [57,58] . Additionally, a number of studies using animal models also report significant effects of prenatal nicotine exposure on BDNF expression in multiple brain regions in both males and females [59][60][61][62] . Lastly, prenatal stress results in decreased BDNF mRNA expression in the frontal cortex and hippocampus, with alterations in DNA methylation at the Bdnf gene proposed as the underlying mechanism [63] .…”
Section: Discussionmentioning
confidence: 99%
“…IV nicotine exposure was largely conducted away from the testing chambers to limit context-drug (conditional stimulus-unconditional stimulus) pairings, and ultimately, context-elicited changes in activity. Lacy et al, (2016) described conditioned hyperactivity in adult male and female rats when saline was substituted for once daily methamphetamine injection, creating a context-only test of activity and demonstrating context-elicited changes in activity. Although associations of contextual cues with nicotine exposure are implicated in the etiology of nicotine dependence (Perkins, 1999; Chaudrhi et al, 2005), the possibility of nicotine-induced contextual conditioning was limited in order to assess the influence of nicotine alone on sensitized behavior.…”
Section: Methodsmentioning
confidence: 99%
“…Baseline sex differences in activity are commonly reported, and females generally exhibit more baseline activity than males (Booze et al, 1999; Kanyt et al, 1999; Zakharova et al, 2012; Lacy et al, 2016; also see Hamilton et al, 2009; Hamilton et al, 2014). Because the primary research question of the current experiment was in regards to the unique influence of chamber shape on nicotine-induced changes in behavior, we first determined if biological sex was a justified covariate by testing for sex differences in baseline activity.…”
Section: Methodsmentioning
confidence: 99%